Analisis Moderasi Good Corporate Governance terhadap Hubungan Antara Solvabilitas dan Kinerja Keuangan Perusahaan Asuransi Syariah di Indonesia - Alfian, Mukhlisul; Atmaji, Atmaji (Riviera Publishing, 2025)
This study aims to analyze the effect of solvency, measured by Risk Based Capital (RBC), on the financial performance of Islamic insurance companies in Indonesia, with Good Corporate Governance (GCG) serving as a moderating variable. Financial performance is proxied by Return on Assets (ROA), while GCG is represented by the number of board of commissioners, board of directors, and sharia supervisory board members. The data used are secondary data obtained from the annual reports of 16 full-fledged Islamic insurance companies registered with the Indonesian Sharia Insurance Association (AASI) during the period 2019–2023. The analysis method employed is panel data regression using the Common Effect Model approach, with robust standard error correction to address classical assumption violations. The results show that solvency (RBC) has a positive and significant effect on financial performance. Additionally, the board of directors and the sharia supervisory board also have a positive influence on ROA. However, moderation is only significant in the interaction between solvency and the sharia supervisory board, while interactions with the board of commissioners and the board of directors are not statistically significant. These findings highlight the importance of strengthening corporate governance based on sharia principles to optimize the financial and operational performance of Islamic insurance firms. This study provides strategic implications for management and regulators in enhancing governance frameworks aligned with Islamic values.